2022
DOI: 10.33715/inonusaglik.1049499
|View full text |Cite
|
Sign up to set email alerts
|

Elaziğ İli̇ndeki̇ 8-15 Yaş Arasi Çocuklarda Hi̇podonti̇ Prevalansinin Değerlendi̇ri̇lmesi̇

Abstract: The aim of this study was to determine the prevalence of congenital tooth deficiencies in permanent teeth (except for the third molars)in the Elazığ province children. In this study, panoramic radiographs of 969 children (473 girls, 496 boys) aged between 8 and 15 years who were admitted to the Department of Pediatric Dentistry of Dentistry Faculty were retrospectively examined. The data obtained from the study were analyzed using descriptive statistics and the Chi-square test and p

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In our study, the rate of missing teeth in the lower jaw was found to be higher than in the upper jaw, and some researchers found the rate of missing teeth to be higher in the mandibula, similar to our study (25,26). There are also studies that found the rate of missing teeth to be higher in the maxilla (4,14).…”
Section: Dıscussıonsupporting
confidence: 89%
“…In our study, the rate of missing teeth in the lower jaw was found to be higher than in the upper jaw, and some researchers found the rate of missing teeth to be higher in the mandibula, similar to our study (25,26). There are also studies that found the rate of missing teeth to be higher in the maxilla (4,14).…”
Section: Dıscussıonsupporting
confidence: 89%
“…Factors at a local level that contribute to the impaction of primary teeth encompass trauma, ankylosis, congenital absence of permanent teeth, abnormalities in the periodontal membrane, odontomas, injuries affecting the periodontal ligament, premature eruption of the first permanent molar, insufficient eruption force, or a combination of these elements. (3,4,5). The frequency of impaction in primary teeth is considered rare (6), with unerupted and impacted premolar teeth being a common condition in children (7).…”
Section: Introductionmentioning
confidence: 99%